Writing Research, Writing Instruction and Educational Research Frontiers and Methodology: An Interview with Steve Graham Download Full PDF - Xinghua Liu (Cranmore Publishing, 2019)
In this interview, Steve Graham talks about his research interests, the importance of writing and his work in developing writing strategies. He responds to critical questions about the writing struggle currently faced by many students in the U.S. and elsewhere and offers possible solutions. He outlines a general picture of writing instruction at the elementary and secondary levels in the U.S. and comments on the impact of Common Core State Standards on writing instruction and research. He further shares his life-long experience in conducting high quality educational intervention research and meta-analyses.